2018
DOI: 10.1080/07391102.2018.1492458
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of deoxyribonucleic acid with deoxyribonucleic acid-binding protein from starved cells: cluster formation and crystal growing as a model of initial stages of nucleoid biocrystallization

Abstract: The paper represents the study of interaction between deoxyribonucleic acid (DNA) and deoxyribonucleic acid-binding protein from starved cells (DPS) cluster formation and crystal growing within a cell. This study is a part of the project that includes European Synchrotron Radiation Facility (ESRF) investigations of in vivo and in vitro nanocrystallization processes of Escherichia coli (E. coli) nucleoid under stress condition combined with theoretical molecular dynamics approaches. Nucleoid biocrystallization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…coli) cells [ 13 , 14 ]. Its structure [ 15 ] and interactions with DNA were recently excessively studied in vitro [ 14 , 16 , 17 ], and in silico [ 18 , 19 ]. Increased synthesis of Dps in the E .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli) cells [ 13 , 14 ]. Its structure [ 15 ] and interactions with DNA were recently excessively studied in vitro [ 14 , 16 , 17 ], and in silico [ 18 , 19 ]. Increased synthesis of Dps in the E .…”
Section: Introductionmentioning
confidence: 99%
“…Dps carries on a regulatory and protective role within Escherichia coli (E. coli) cells [13,14]. Its structure [15] and interactions with DNA were recently excessively studied in vitro [14,16,17], and in silico [18,19]. Increased synthesis of Dps in the E. coli cells occurs in the stationary phase, under starving conditions, allowing for the protection of DNA from oxidative stress, heat, acid, alkaline shock, toxic effects of heavy metals, antibiotics, UV radiation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…During starvation, Dps is very active and can greatly alter the structure of bacterial DNA. Its structure [21] and interaction with DNA have recently been studied in vitro [21,22] and in silico [23,24]. Dps is a dodecamer consisting of 12 identical chains [21].…”
Section: Bacterial Growth Dps Proteinmentioning
confidence: 99%
“…The structure of this protein and probable interactions with DNA was studied in vitro [6,7,9,16,26,34]. In silico studies have shown how the DPS protein can form crystals and co-crystals with DNA under various conditions [36][37][38]. The long N-terminal regions and the surface of the protein are rich in lysine residues.…”
Section: Introductionmentioning
confidence: 99%